Hubungan Pengetahuan Dengan Keteraturan Pemeriksaan Antenatal Care Pada ibu hamil TM III diwilayah Kerja Puskesmas Telaga Dewa Kota Bengkulu Tahun 2025 - Dilen Yohana; Yesi Putri; Danur Azissah (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The Maternal Mortality Rate (MMR) in Indonesia remains a serious health issue. According to the 2023 Indonesian Health Survey (SKI), the MMR reached 189 per 100,000 live births. One important effort to reduce the MMR is through regular Antenatal Care (ANC) checkups. However, the national coverage of complete ANC visits (K6) has only reached 80.47%, still below the 100% target. The regularity of ANC visits is influenced by various factors, one of which is the level of knowledge of pregnant women. This study aims to determine a correlation between the knowledge of pregnant women and the regularity of Antenatal Care (ANC) visits in third trimester pregnant women in the Working Area of Telaga Dewa Health Center, Bengkulu City, in 2025. This study used a quantitative design with a cross-sectional approach. The study sample consisted of 60 third trimester pregnant women selected using purposive sampling. Data were collected through knowledge questionnaires and maternal and child health (MCH) books to assess regularity of ANC visits. Data analysis was performed using the Chi-Square test. The results showed that 65.0% of respondents had good knowledge and 66.7% attended ANC visits regularly. Statistical tests showed a p-value of 0.004 (p < 0.05) with an Odds Ratio (OR) of 5.16. This indicates a significant correlation between the knowledge of pregnant women and the regularity of ANC visits. This study concluded that there is a significant correlation between pregnant women's knowledge and the regularity of ANC visits, so that increasing pregnant women's knowledge plays an important role in increasing the regularity of ANC visits and supporting efforts to reduce the Maternal Mortality Rate.